HUBUNGAN SIKAP DAN MOTIVASI BELAJAR DENGAN HASIL BELAJAR MATEMATIKA KELAS IV A - Ela Riska Aulia; Suparjan Suparjan; Rio Pranata (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractRelationship learning attitudes and learning motivation with mathematics learning outcomes in grade IV A. The research method used is descriptive method of preliminary study research. The population in this study amounted to 24 students and the sample used was class IV A totaling 24 students. Data collection techniques study are indirect communication techniques and documentary study techniques. The instrument of this study was in the form of a questionnaire and a mid-semester math test score document. The results showed that student learning attitudes at amounted to 72.55% in the "Enough" category and 78.43% student motivation in the "Good" category. While the mid-semester math test scores for students obtained an average of 79.37 in the "Good" category. Based on the results of statistical calculations using the multiple relationship formula to calculate the relationship between learning attitudes and learning motivation with student learning outcomes, it is obtained r count of 0.368, while rtable for N = 24 and a significance level of 5% of 0.404 means rcount < rtable or 0.368 < 0.404. Based on the results of the study, the relationship between learning attitudes and learning motivation with mathematics learning outcomes for grade IV A students is in the low category.Keywords: Relationship, Learning Attitude, Learning Motivation, Mathematics Learning Outcomes